2008
DOI: 10.1139/f07-175
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the impacts of water management on aquatic communities

Abstract: Systematic meta-analyses were conducted on the ecological impacts of water management, including effects of (i) dewatering on macroinvertebrates, (ii) a hypolimnetic release on downstream aquatic fish and macro invertebrate communities, and (iii) flow modification on fluvial and habitat generalists. Our meta-analysis indicates, in general, that (i) macroinvertebrate abundance is lower in zones or areas that have been dewatered as a result of water fluctuations or low flows (overall effect size, –1.64; 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 40 publications
0
102
1
Order By: Relevance
“…2) (DeLonay, Chojnacki, Jacobson, Albers, and others, 2016). Empirical evidence suggests that dam-induced thermal alteration has substantial implications for stream productivity and the growth of organisms (Haxton and Findlay, 2008). Increasing water temperature in some aquatic systems has been positively correlated with rates of primary productivity (Winemiller, 2004) and secondary production of aquatic invertebrates (Plante and Downing, 1989).…”
Section: Lines Of Evidence To Support Action Hypothesismentioning
confidence: 99%
“…2) (DeLonay, Chojnacki, Jacobson, Albers, and others, 2016). Empirical evidence suggests that dam-induced thermal alteration has substantial implications for stream productivity and the growth of organisms (Haxton and Findlay, 2008). Increasing water temperature in some aquatic systems has been positively correlated with rates of primary productivity (Winemiller, 2004) and secondary production of aquatic invertebrates (Plante and Downing, 1989).…”
Section: Lines Of Evidence To Support Action Hypothesismentioning
confidence: 99%
“…Some studies have showed that dam-induced thermal alterations have significant implications for stream productivity and the reproduction, growth, distribution and assemblage of organisms (Haxton and Findlay, 2008). Generally the biodiversity downstream of a dam is lower than in natural environments because of a reduced temporal heterogeneity in flow and temperature regime (Ward and Stanford, 1983;Jakob et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Interpreting results and drawing conclusions 8 There are some common types of bias that can occur in many different study designs. In health care research these are often classified as selection, performance, detection, attrition and reporting biases.…”
Section: Presenting Data and Resultsmentioning
confidence: 99%